1999
DOI: 10.1021/ic981237n
|View full text |Cite
|
Sign up to set email alerts
|

[Co4O4]4+ Cubane Core as a Brønsted Base:  Preparation and Properties of [Co4O3(OH)(O2CR)2(bpy)2]3+ and [Co4O2(OH)2(O2CR)2(bpy)2]4+ Salts

Abstract: The cover picture shows the structure transformation from a well-known gold nanocluster Au 25 (SCH 2 CH 2 Ph) 18 (Au 25 for short) to a novel cadmium doped gold nanocluster [Au 13 Cd 2-(PPh 3) 6 (SC 2 H 4 Ph) 6 (NO 3) 2 ] 2 Cd(NO 3) 4 (Au 26 Cd 5 for short) by a combined peeling and doping process. Although the mother nanocluster Au 25 is inactive, the as-prepared Au 26 Cd 5 exhibits high catalytic activity, as well as good recyclability and sub-strate tolerance at room temperature. The high catalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 36 publications
8
13
0
Order By: Relevance
“…3, a) due appar ently to intermolecular antiferromagnetic exchange interactions. This behavior strongly differs from the magnetic prop erties of the known symmetrical cubane [Co 4 (µ 3 OMe) 4 (µ 2 OOCBu t ) 2 (η 2 OOCBu t ) 2 (MeOH) 4 ]•4MeOH (8), 11 which we synthesized according to the new method by recrystallization of the tetranuclear complex [Co 4 (µ 3 OH) 2 (µ 2 OOCBu t ) 4 (η 2 OOCBu t ) 2 (EtOH) 4 ]•2EtOH with the planar metal core from methanol. 28 According to the results of magnetic measurements, the effective magnetic moment of complex 8 monotoni cally decreases throughout the 300-2 K temperature range from 9.82 to 4.20 µ B due to spin orbital and spin spin antiferromagnetic exchange interactions (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…3, a) due appar ently to intermolecular antiferromagnetic exchange interactions. This behavior strongly differs from the magnetic prop erties of the known symmetrical cubane [Co 4 (µ 3 OMe) 4 (µ 2 OOCBu t ) 2 (η 2 OOCBu t ) 2 (MeOH) 4 ]•4MeOH (8), 11 which we synthesized according to the new method by recrystallization of the tetranuclear complex [Co 4 (µ 3 OH) 2 (µ 2 OOCBu t ) 4 (η 2 OOCBu t ) 2 (EtOH) 4 ]•2EtOH with the planar metal core from methanol. 28 According to the results of magnetic measurements, the effective magnetic moment of complex 8 monotoni cally decreases throughout the 300-2 K temperature range from 9.82 to 4.20 µ B due to spin orbital and spin spin antiferromagnetic exchange interactions (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Tetra(µ µ µ µ µ 3 hydroxo)tris(η η η η η 1 trimethylacetato)tris(µ µ µ µ µ 4,5 di methyl 1,2 phenylenediamino)tris(η η η η η 1 4,5 dimethyl 1,2 phe nylenediamino)tetracobalt(II) trimethylacetate ethanol and water solvate, [Co 4 (µ µ µ µ µ 3 OH) 4 (η η η η η 1 OOCBu t ) 3 (µ µ µ µ µ (NH 2 ) 2 C 6 H 2 Me 2 ) 3 ( η η η η η 1 (NH 2 ) 2 C 6 H 2 Me 2 ) 3 ] + (OOCBu t ) -•4EtOH•1. 4 (µ 2 OOCBu t ) 2 (η 2 OOCBu t ) 2 (MeOH) 4 ]•4MeOH determined earlier by X ray diffraction. 11 Tetra(µ µ µ µ µ 3 methoxo)bis(µ µ µ µ µ 2 O,O´ trimethylacetato)bis (µ µ µ µ µ 2 O,O´ trimethylacetato)tetra(η η η η η 1 methanol)tetranickel(II) methanol tetrasolvate, [Ni 4 (µ µ µ µ µ 3 OMe) 4 (µ µ µ µ µ 2 OOCBu t ) 2 (η η η η η 2 OO CBu t ) 2 (MeOH) 4 ]•4MeOH (9•4MeOH).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…2 Tetranuclear cubane-like nickel complexes have been extensively investigated since the pioneering work of Andrew and Blake et al 3 A number of cubanelike tetranuclear nickel complexes involving bridging OH 4 or OMe, 5 or alkoxo 6,7 have been pre-viously reported. Jezowska-Trzebiatowska and coworkers 8 reported a nickel(II) complex of 2-hydroxymethyl-Nsalicylideneaniline (H 2 L), and concluded that the complex had a polynuclear structure.…”
Section: Introductionmentioning
confidence: 99%